Management of isolated syringomyelia in the paediatric population – a review of imaging and follow-up in a single centre. (October 2013) - Joseph, R. N.; Batty, R.; Raghavan, A.; Sinha, S.; Griffiths, P. D.; Connolly, D. J. A.
Abstract Objective. To assess the natural history of isolated syringomyelia in children. Methods. MRI reports from February 2007 to August 2011 mentioning syrinx were identified on Sheffield Children's PACS database. Scans with syringes having an AP diameter of > 1 mm and extending over at least two vertebral bodies were reviewed. Patients with an identifiable cause such as a Chiari malformation were then excluded. Results. Thirty-nine patients were included with a mean age at diagnosis of 10.6 years. The average syrinx AP diameter was 3.30 mm. The rostrocaudal length of the syringes varied between 2 and 19 vertebral bodies. Twenty-seven out of 39 syringes were thoracic in origin. There were 3 and 6 syringes involving the cervicothoracic and thoracolumbar regions, respectively, with 3 involving the cervical area only. Eleven out of 39 (Group I) patients were found "incidentally" during work-up for adolescent idiopathic scoliosis and these were considered as a separate group. These patients did not have any significant symptoms and were discharged following their scoliosis correction surgery. Syrinx was incidental in 14 further patients (Group II). Of the 14 patients, 11 remained asymptomatic with no change in syrinx morphology throughout follow up. Of the 14 patients, 3 were lost to follow-up. Of the 39 patients, 14 (Group III) presented with progressive back pain without any obvious clinical cause. Of the 14, 10 either improved or remained the same. Of the14 patients, 3 underwent lumbar puncture, 1/14 having myelography. All 4/14 patients reported significant pain reduction on follow up following intervention. Conclusion. Idiopathic syrinx is a benign pathology, which can be managed expectantly. Most cases remain stable or improve over time. In a small minority who have progressive back pain, we have found that lumbar puncture may be helpful in reducing symptoms.